Effects of Thiobacillus Ferrooxidans on corrosion of AISI 4140 Steel in presence of oil biodiesel (2014)
In this paper we study the behavior of microbiologically induced corrosion by means of specie Thiobacillus ferrooxidans on AISI 4140 Alloy Steel with chromium and molybdenum high hardenability and good fatigue resistance, abrasion and impact influenced by Thiobacillus ferrooxidans. To determine the effect of process variables, speed and type of corrosion adhesion. The corrosion products formed on the surface of the samples using scanning electron microscopy were analyzed. The results showed the appearance of pinholes in the surface steel AISI 4140- after 24, 72, 120 and 168 hours of exposure in solution with the presence of Thiobacillus ferrooxidans, which was induced by the metabolism of bacteria, showing the presence of bacteria to accelerated the process of localized corrosion in the steel sample AISI 4140.